Muscular Strength is Independently Associated with Cystatin C: The KORA-Age Study - Volaklis, Konstantinos; Thorand, Barbara; Peters, Anette; Halle, Martin; Margot, Heier; Amann, Ute; Ladwig, Karl Heinz; Schulz, Holger; Koenig, Wolfgang; Meisinger, Christa (International Journal of Sports Medicine, 2018)
The purpose of this study was to investigate if there is a link between muscular strength (MS) and markers of chronic kidney disease (CKD) among older adults. The cross-sectional analysis based on 1041 men and women, aged 65–94 years, who participated in the KORA-Age study. Participants underwent an interview and extensive examinations including anthropometric measurements, diseases and drug intake registration, determination of health-related behaviors, collection of blood samples for measurements of cystatin C and maximal muscle strength evaluation. One-Way ANOVA revealed significant differences in both mean cystatin C (1.16±0.37 vs. 1.03±0.29 vs. 0.93±0.24 mg/L, p<0.001) and mean eGFRcysC (63.61±18.61 vs. 72.14±18.92 vs. 79.87±18.19 ml/min/1.73 m2, p<0.05) across thirds of maximal muscular strength (from lowest to highest). MS in the lowest third was significantly associated with increased odds of having elevated cystatin C (OR: 1.70, 95% CI: 1.01–2.85, p=0.043) after controlling for age, gender, fat mass, fat-free mass, alcohol intake, smoking status, number of regularly used medications, multimorbidity status, hs-CRP, telomere length and levels of physical activity. Lower levels of MS are independently associated with higher concentrations of cystatin C and lower eGFRcysC in older individuals. Increasing the levels of muscular strength may be useful to prevent the age-related CKD disease of older adults.
Keywords: muscular strength; chronic kidney disease; cystatin C; older adults